Beyond Oil: Leveraging Community-Based Eco-Tourism for Sustainable Development and Biodiversity Conservation in Nigeria’s Niger Delta Region - Maxwell-Borjor Achuk Eba (Universitas Negeri Makassar, 2025)
The Niger Delta region of Nigeria, long synonymous with petroleum extraction and environmental degradation, possesses vast untapped potential for eco-tourism, centered on its unique mangrove ecosystems, rich biodiversity, and cultural heritage. This paper argues that a strategically developed, community-based eco-tourism model can serve as a catalyst for sustainable development, providing an alternative livelihood to mitigate poverty and reduce dependence on extractive industries. Through a mixed-methods approach incorporating stakeholder interviews, geographic surveys, and case study analysis, the research assesses the current state of eco-tourism initiatives in the region, identifies key ecological and cultural assets, and examines the major barriers to development including infrastructure deficits, security concerns, and lack of local capacity. The study concludes by proposing a integrative framework for eco-tourism development that prioritizes community ownership, ecological preservation, and pro-poor economic benefits, thereby contributing to the broader goals of environmental restoration and social stability in the Niger Delta